Muscle strength and damage following two modes of variable resistance training - Aboodarda, S.J.; George, J. (2011)
Nautilus Machine (NM) and Elastic Resistance (ER) have gained considerable popularity among athletes and recreational lifters seeking to increase muscle strength. However, there is controversy concerning the use of ER for increasing muscle hypertrophy and strength among healthy-trained individuals. The aim of the study was to compare the effect of repeated near maximal contractions by ER/NM on indicators of muscle damage including: maximal strength decrement (MVIC), rate of muscle soreness (DOMS), concentration of plasma creatine kinase (CK) and increased high muscle signal on T2 weighted images using magnetic resonance imaging (MRI). Nine healthy male subjects completed two modalities of exercise (5 sets × 10RM ER/NM) in a counterbalance cross-over study design with three weeks “wash-out” period between experiments. The MVIC was measured and DOMS rated and recorded for 4 consecutive days while blood samples were collected on day 1, 3, 5 and 7. Prior to and forty eight hours after completion of each mode of exercise, subjects underwent MRI scanning. The average of applied forces demonstrated significantly higher value for NM compared with ER (362 ± 34.2 N vs 266.73 ± 44.6 N respectively) throughout the 5 sets of dynamic exercise (all p <0.05). However, the indicators of muscle damage (T2 relaxation time, DOMS, MVIC and serum CK) exhibited a very similar response across both modes of training. Plasma CK increased significantly following both modes of training with the peak value on Day 3 (p < 0.05). The time course of muscle soreness reached a significant level after both modes of exercise and showed a peak value on the 2nd day (p < 0.05). The T2 relaxation time demonstrated a statistically significant increase following ER and NM compared with the pre-test value (p < 0.05). The similarity of these responses following both the ER and NM exercise training session suggests that both modes of training provide a similar training stress; despite a considerably lower external force generation during ER. The importance of these findings is underlined by the fact that exercise-induced muscle damage has been shown to be the underlying mechanism of further muscle hypertrophy.